Empowerment and Provision of Early Health Education to Children in Orphanages - Ramdhan, Dadan; Ramadhanti, Suci; Nurmughni Nabilatuzaman, Nada; Asti Putri Bunyamin, Nun; Kusumah Wn, Uning; Iswanto, Riki; Herlinda, Herlinda (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
This Community Empowerment Program involves delivering education on handwashing techniques and raising awareness about the dangers of drugs to children living in the Ar-Ridho Orphanage. Consisting of three stages, namely planning, implementation, and evaluation, this service successfully generated enthusiasm among the participants during the delivery of the materials and handwashing practice sessions. Good information absorption occurred because the material was tailored to their age. Socialization about drugs was also conducted with the aim of providing understanding of their dangers and encouraging them to stay away from drugs from an early age. This activity combines delivering material about drugs with interactive games and quizzes, strengthening the children's understanding of the risks of drug abuse. The results are expected to enhance their understanding and foster a spirit to stay away from drug abuse. Throughout the socialization process, the participants showed enthusiasm both when listening to the material and when practicing proper handwashing. This is because of the use of strategies, methods, and media tailored to their age, allowing participants to understand the socialization material well during this service. Therefore, there is a need for ongoing supervision from the caretakers at the orphanage to ensure the absorption of the taught material.